Peran Pondok Persulukan Babussalam Baru Sei Titi An-Nur dalam Membangun Akhlakul Karimah Masyarakat Desa Huta Baru Kecamatan Simangambat Padang Lawas Utara - Harahap, Jainuddin (UIN Sumatera Utara, 2024)
Based on the results of interviews and analysis of the role of the New Babussalam Sei Titi An-Nur Sulukan Lodge in building the Akhlakul Karimah community in Huta Baru Village, it can be concluded that the religious practice of Sufism in the formation of Akhlakul Karimah in the New Babussalam Sei Titi An-Nur Sulukan Hut in Huta Baru Village. According to the results of an interview conducted by the author with the head of Pondok Persulakan Babussalam Baru Sei Titi An-Nur, Huta Baru village, Khalifa Makmur Siregar said that